EFFECT OF PEOPLE BASED LEADERSHIP ON MOTIVATION TO PERFORM JOB - Azman Ismail; Ishak Abd Rahman; Asyakireen Samsudin; Alvianny Voo Nyuk Chong @ Albertus, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study measures the relationship between people-based leadership and motivation to perform using self-report questionnaires collected from the staff at a government research university in Peninsular Malaysia. The results of stepwise regression analysis confirm that participative and consultative styles were significantly correlated with motivation to perform a job. This result demonstrates that the ability of leaders to appropriately implement participative and consultative styles in performing daily job operations have increased employees’ motivation to perform a job in the studied organization. Additionally, this study offers discussion, implications, and conclusions.